Effectiveness of The Role of Sms/Whatsapp Reminders, Blood Pressure Self-Monitoring, and Preeclampsia Education on The Early Detection of Gestational Hypertension At Kosambi Clinic, Tangerang, Tangerang, in 2025 - Abela Mayunita; Yana Karunia Hastuti (Jurnal Ners, 2026)
Surgery is an invasive medical procedure performed by opening a specific body part, usually through an incision, for the purpose of treating or correcting a pathological condition. In this procedure, the body part requiring surgery is opened for repair according to medical indications. Once the repair is complete, the incised area is then sutured to restore tissue integrity (Wekoadi et al., 2018)Finger-holding therapy, or finger-holding relaxation, is a form of relaxation therapy derived from the Japanese acupressure technique known as Jin Shin Jyutsu. This technique involves gentle finger touches combined with slow, controlled breathing to help balance the flow of energy within the body. Each finger and palm are believed to be associated with specific emotional and energetic states. The process of gently holding fingers can create a warm sensation in the hands, which has a calming effect and helps create a feeling of relaxation and comfort. This effect plays a role in helping relieve anxiety, reduce tension, and alleviate symptoms such as headaches (Adani and Kurniawan, 2023).The type of research used is quantitative, with a pre-experimental design (one-group pre-post test), which involves measuring the effect of the finger hold relaxation technique in reducing pre-operative patient anxiety before and after the intervention.Bivariate analysis using the Wilcoxon Signed Ranks Test showed a significant difference between anxiety levels before and after the finger-hold relaxation technique intervention, with a p-value of 0.000 (p < 0.05). This result indicates that the reduction in anxiety levels following the intervention was statistically significant. All respondents experienced a decrease in anxiety scores after the intervention, indicating that the finger-hold relaxation technique provided relaxation, increased calm, and helped patients manage anxiety before undergoing surgery.The finger-holding relaxation technique has various benefits, including helping reduce pain, fear, and anxiety, calming the mind, improving emotional control, providing a sense of comfort, and improving blood flow. Therefore, this technique can be used as a simple, safe, and easy-to-implement non-pharmacological intervention in nursing practice (Hartono et al., 2021). This is consistent with research by Indrawati (Yade Kurnia Sari & Septa Nelli, 2024), which explains that holding fingers while taking deep breaths can reduce and even heal physical and emotional tension. This finger-holding relaxation technique warms the energy entry and exit points in the meridians (energy pathways within the body) located in the fingers. This then provides a spontaneous stimulation effect when held. This stimulation then flows to the brain and then continues to the nerves in the affected organ, hopefully clearing blockages in the energy pathways.